Rheological and thermal properties of palm kernel shell filled low density polyethylene composites - Lim, Bee Ying (Universiti Malaysia Perlis (UniMAP), 2014)
The palm kernel shell (PKS) filled low density polyethylene (LDPE) composites were prepared by Z-blade mixer at temperature of 180 °C and rotor speed of 50 rpm. The effects of PKS loading and different types of chemical modifications on the rheological and thermal properties of the composites were studied. Chemical modification such as poly(ethylene-co-acrylic acid) (PEAA), acrylic acid (AA), 3- aminopropyltriethoxysilane (3-APE), coconut oil coupling agent (COCA) and ecodegradant were used in this study. The addition of PKS into LDPE matrix changed the rheological and thermal properties of the composites. The results showed that increasing PKS loading had decreased the melt flow index (MFI) values and non-Newtonian index but increased the melt consistency, viscosity and activation energy of the LDPE/PKS composites. The increasing temperature had increased the MFI values of composites. The viscosity of composites that was generated from capillary rheometer decreased with rise of temperature. The apparent shear stress of the composites increased with apparent shear rate and PKS loading. The composites with addition of PEAA, AA, COCA and eco-degradant showed higher MFI values but the composites treated with 3-APE exhibited lower MFI values than untreated composites. The activation energy for the composites with PEAA and 3-APE decreased, whereas the activation energy for the composites with AA, COCA and eco-degradant increased as compared to composites without chemical modifications. The composites with eco-degradant gave lowest viscosity, thus eased the composite processing at high filler loading. The thermal properties of composites showed that addition of PKS had decreased the onset temperature and the total weight loss of composites. The chemical modifications had increased the thermal stability of composites, whereas higher onset temperature and lower total weight loss at high temperature were observed. The FTIR spectra of composites showed that the functional groups of the composites changed with chemical modification.